2020
DOI: 10.1038/s41598-020-77260-2
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activity and strength are reflected by changes in the post-synaptic secretory pathway

Abstract: Neurons are highly asymmetric cells that span long distances and need to react promptly to local demands. Consequently, neuronal secretory pathway elements are distributed throughout neurites, specifically in post-synaptic compartments, to enable local protein synthesis and delivery. Whether and how changes in local synaptic activity correlate to post-synaptic secretory elements is still unclear. To assess this, we used STED nanoscopy and automated quantitative image analysis of post-synaptic markers of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Interestingly, at the 72 h timepoint where the most puncta were observed, we did not observe increased intensity (Fig. 3b), perhaps indicating less functional/active 51 or dormant synapses 52 . Representative Airyscan images of dendrites at 3 h, 72 h and controls are illustrated in Fig.…”
Section: Biphasic Regulation Of Presynaptic Synapsin-1 By Psilocybin ...mentioning
confidence: 73%
See 2 more Smart Citations
“…Interestingly, at the 72 h timepoint where the most puncta were observed, we did not observe increased intensity (Fig. 3b), perhaps indicating less functional/active 51 or dormant synapses 52 . Representative Airyscan images of dendrites at 3 h, 72 h and controls are illustrated in Fig.…”
Section: Biphasic Regulation Of Presynaptic Synapsin-1 By Psilocybin ...mentioning
confidence: 73%
“…Psilocybin is currently investigated as an adjuvant therapy to other modes of treatment, and by nding the optimal timing between psilocybin treatment, and for instance therapy, the effect might be even larger. Increased uorescent intensity levels of synaptic puncta expression have previously been correlated to increased levels of functional synapses 50 as well as post-synaptic machinery necessary for active synapses 51 . Intensity levels of Homer1, Piccolo, and Synapsin-1 puncta mirror the increased numbers of puncta we observe, with the exception of 72 h post-psilocybin treatment for Synapsin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further established this link at the synapses themselves. To do so, they labeled actively recycling synaptic vesicles using antibodies against the lumenal domain of synaptotagmin1 (Syt1) as a proxy for local synaptic activity (Kraszewski et al, 1996 ; Wilhelm et al, 2010 ; Truckenbrodt et al, 2018 ; Gürth et al, 2020 ). Using stimulated emission depletion (STED) microscopy, they confirmed that local synaptic activity is significantly correlated to the extent of recycling.…”
Section: Recycling Of Synaptic Ecmmentioning
confidence: 99%
“…While this is the only demonstration, to our knowledge, of a complete recycling loop of an ECM molecule, many additional studies also add credence to the concept of ECM recycling at synapses. These include reports of ECM molecules that undergo internalization (e.g., Coopman et al, 1996 ; Tammi et al, 2001 ; Shi and Sottile, 2008 ; Lobert et al, 2010 ; Leonoudakis et al, 2014 ), demonstrations that ECM receptors are present at synapses (e.g., Kramár et al, 2002 ; Huang et al, 2006 ; Roszkowska et al, 2016 ; Izumi et al, 2017 ; Apóstolo et al, 2020 ; Briatore et al, 2020 ), and reports that synapses contain the machinery for trafficking recycling molecules in an activity-dependent manner (Tang, 2008 ; Gürth et al, 2020 ; Helm et al, 2021 ). Nevertheless, additional demonstrations of the recycling of ECM molecules in neurons are anticipated in the future.…”
Section: Recycling Of Synaptic Ecmmentioning
confidence: 99%